Green synthesis of CuO nanoparticles from Punica granatum leaves and their application in the enhancement of cold-pressed calcareous alkali-activated materials for sustainability - Meera Salama; Pwadubashiyi Coston Pwavodi (PLoS ONE, 2025)
The green synthesis of metal nanoparticles using plant extracts offers an environmentally friendly approach that reduces energy consumption and avoids hazardous chemicals, thus increasing various sustainable applications. This study investigates the green synthesis of copper oxide nanoparticles (CuO nanoparticles) using extracts from pomegranate ( Punica granatum ) leaves and their application in enhancing calcareous alkali-activated materials (AAMs). Characterization techniques, including Ultraviolet-Visible spectroscopy (UV-Vis), Fourier-Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Dynamic Light scattering (DLS), and Transmission Electron Microscopy (TEM), were employed. CuO nanoparticles were incorporated into cold-pressed AAMs at varying concentrations (0.25%, 0.5%, and 1% by weight). Mechanical and physical properties such as compressive strength, porosity, and water absorption were evaluated, followed by microstructural analysis using XRD, FTIR, Scanning Electron Microscopy (SEM), and Energy-Dispersive X-ray Spectroscopy (EDX). The synthesized CuO nanoparticles exhibited high crystallinity with minor amorphous content and a narrow size distribution, with an average particle size of 78 nm. The incorporation of 0.5% CuO nanoparticles yielded optimal results, increasing compressive strength (UCS) by 37.3% and reducing porosity and water absorption by 0.75% and 0.4%, respectively, compared to the control. Microstructural analysis indicated that CuO nanoparticles enhance matrix compactness and promote the formation of alkali-activated binder phases. Overall, the findings demonstrate that Punica granatum leaf extract can be effectively used for the green synthesis of semi-spherical CuO nanoparticles (<100 nm) with good stability. Their incorporation into calcareous AAMs significantly improves matrix densification and mechanical performance.